CODE MIXING USED BY IQBAAL RAMADHAN ON THE HAHAHA TV YOUTUBE CHANNEL - Aryani, Fadhilla Arum; Budiwaty, Suci (UG Journal, 2024)
This research investigates the types and motives of code-mixing employed by Iqbaal Ramadhan in the YouTube videos "Iqbaal Ramadhan: '3x Ditolak Idola Cilik' - IN-FRAME w/ Ernest Prakasa" and "Iqbaal Ramadhan: 'Nggak Mau Kerja Demi Uang' - IN-FRAME w/ Ernest Prakasa". Utilizing qualitative methodology, the study applies Muysken's (2000) code-mixing theory to categorize the types of code-mixing and Hoffmann's (1991) theory to analyze the underlying motives behind Iqbaal Ramadhan's code-mixing instances. The analysis reveals the presence of all three types of code-mixing, including insertion, alternation, and congruent lexicalization, with a total of 101 instances identified. Furthermore, seven distinct motives for code-mixing are identified, namely talking about particular topics, expressing group identity, clarifying speech content for interlocutor comprehension, repetition for clarification, emphasis, interjections, and quoting external sources. Keywords: code-mixing, Iqbaal Ramadhan, YouTube videos